Design analysis, installation and performance evaluation of a hydraulic ram pump system with a modified waste valve - Jr, Danilo P. Metra,; Credo, Marvin C. (Vietnam Journal of Science and Technology, 2020)
Hydraulic ram pump is one of the oldest mechanical devices used for water lifting. A hydraulic ram pump has two moving parts which are the waste valve and delivery valve. As a lot of studies had been carried out investigating parameters possibly affecting the performance of a hydraulic ram pump, this study aimed to design and fabricate a modified waste valve for a hydraulic ram pump with parts made from locally available off-the-shelf materials. Results revealed that varying the height of the waste valve’s stroke significantly affected the relivery flow rate thus affecting its overall all efficiency.